Response of Alfalfa Yield to Rates and Ratios of N, P, and K Fertilizer in Arid and Semi-Arid Regions of China Based on Meta-Analysis - Huipeng Ren; Songrui Ning; An Yan; Yiqi Zhao; Ning Li; Tingting Huo (Agronomy)
Quantifying the impacts and contributions of nitrogen (N), phosphorus (P), and potassium (K) fertilizer management on the annual and cutting cycle yields of alfalfa can provide guidance for alfalfa cultivation. In this study, 597 sets of alfalfa yield data from the arid and semi-arid regions of China were collected and grouped according to the N, P, K, and NPK rates. Statistical and meta-analyses were employed to explore the response of alfalfa yield to fertilization management. The results indicated that the annual and cutting cycle yields of alfalfa increased and then decreased as the N rate increased; meanwhile, the annual yield increased with the P and K rates, and the cutting cycle yield decreased with increased cutting cycles under P and K treatments. The alfalfa yield at the first cutting cycle was about 30% of the annual yield in the arid and semi-arid regions of China. Moreover, the annual yield increased and then decreased as the NPK rate increased. The Aggregated Boosted Tree (ABT) algorithm-based analysis showed that the NPK rate had the greatest contribution to the annual yield (37.61%), followed by the application rates of P (24.50%), N (22.55%), and K (15.34%). The impacts of the P/NPK, N/NPK, and K/NPK ratios on the annual yield were 38.64%, 31.71%, and 27.65%, respectively. Additionally, an NPK amount > 225–310 kg/ha and ratios of N, P, and K of 14.28–27.72%, 36.36–50%, and below 25%, respectively, resulted in the highest increase in alfalfa yield. This is recommended as the optimal fertilization practice to obtain high alfalfa yields and improve fertilizer use efficiency in the arid and semi-arid regions of China.